Beginning and experienced secondary school teachers' self- and student schema in positive and problematic teacher–student relationships. (April 2016) - Claessens, Luce; van Tartwijk, Jan; Pennings, Helena; van der Want, Anna; Verloop, Nico; den Brok, Perry; Wubbels, Theo
Abstract: The quality of teacher–student relationships is important for teachers' well-being in schools. In this interview study we investigated which cognitions comprise secondary school teachers' self- and student schema in positive and problematic teacher–student relationships. Frequency analyses of these cognitions showed that especially student schema differed in teachers' talk of positive and problematic relationships. When combining cognitions of the self- and student schema, a HOMALS analysis revealed two types of positive and two types of problematic relationships. Differences between novices and experienced teachers were apparent for positive relationships. These findings raise questions about teachers' attributions for the quality of teacher–student relationships. Highlights: In teachers' accounts of positive and problematic relationships, student schemas differ more than self-schemas. Especially student agreeableness, motivation and interpersonal behaviour differ in positive and problematic relationships. Novices and experienced teachers mainly differ in their accounts of positive relationships.